Discovery of a role of the novel hepatokine, hepassocin, in obesity - Huang, Ru‐Lai; Li, Chung‐Hao; Du, Ye‐Fong; Cheng, Kai‐Pi; Lin, Ching‐Han; Hu, Che‐Yuan; Wu, Jin Shang; Chang, Chih‐Jen; Wu, Hung‐Tsung; Ou, Horng‐Yih (BioFactors (Oxford), 2020)
Obesity is a public health problem that has raised concerns worldwide and is often associated with hepatic steatosis. Hepassocin is a novel hepatokine that causes hepatic steatosis and induces insulin resistance (IR). However, the role of hepassocin in obesity remains obscure. Thus, the aim of this study was to investigate the relationship between hepassocin levels and obesity. In total, 371 subjects who had a normal weight (NW), were overweight, or were obese were enrolled. We found that hepassocin levels in subjects who were overweight (6,705 ± 1,707 pg/ml) or obese (7,335 ± 2,077 pg/ml) were significantly higher than those of subjects with a NW (5,767 ± 1,500 pg/ml) (p < .001, test for trend). A multiple linear regression analysis showed that the body‐mass index, waist circumference, nonalcoholic fatty liver disease, and homeostatic model assessment of IR were independently associated with hepassocin after adjusting for age, sex, high‐sensitivity C‐reactive protein, systolic blood pressure, high‐density lipoprotein‐cholesterol, log triglycerides, alanine transaminase, and the estimated glomerular filtration rate. This study provides evidence that subjects who were overweight or obese had significantly higher hepassocin levels than those with a NW. Hepassocin may be a useful biomarker in managing obesity and its related metabolic dysregulation.